Key Agreement Procotol in DSN - Jian Zhou; Xianwei Zhou (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In space networks, the long time delay, large scale and maintainability of difficultly nature makes key management more difficult than ground wireless networks. The main challenge is how to handle 1-affects-n problem that become more serious as entities spread over a wide geographic area. To solve it, this paper proposes a one-to-many mapping shared key agreement, which is based on one-to-many encryption mechanism model. In the proposed key agreement, each entity has different decryption key and shares an encryption key. When an entity joins or leaves network, updated keys only are public encryption key and its decryption key. However, the other entities’ secret key remains unchanged, so as to each member has the ability to update key autonomously. Consequently the performance of the proposed key management scheme is unrelated to the network scale, node mobility and topology structure. It is shown that our proposed key management scheme not only improves the efficiency and flexibility for space networks, but also achieves good security properties, including forward security and backward security and many more by theoretical analyses. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2029